Prevalence of astigmatism in children treated in a hospital in the Peruvian highlands - Valencia-Chuquillanqui, Milagros (2022)
Objetive. To calculate the prevalence of astigmatism in children aged 3 to 10 years seen in the ophthalmology service of the Hospital Regional Docente Materno Infantil El Carmen, Huancayo, Peru. Methods. The study approach was quantitative, descriptive, retrospective and cross-sectional. The census population consisted of 100 medical records of pediatric patients. The medical records were reviewed to assess astigmatism (red reflex, visual acuity determined by Snellen chart and ocular motility). A descriptive analysis of frequencies and percentages was performed. Results. A 64% prevalence of astigmatism was found in the study sample. Conclusions. It determines that the prevalence found in the present study is higher compared to other studies consulted.